First in 109 years: Catalogue of scarab beetles (Coleoptera: Scarabaeidae) of the Philippines - Magallanes, Joriemar G.; Nuñeza, Olga M.; Mondejar, Eddie P. (Zootaxa, 2026)
More than a century ago, Wilhelm Schultze published his seminal work, A Catalogue of Philippine Coleoptera, documenting over 290 species of scarab beetles. Since then, no comprehensive updates have been made. This catalog seeks to provide an exhaustive record of all scarab species reported in the Philippines from the early 1800s to the present. Currently, scarab beetles in the country are represented by seven subfamilies, 104 genera, and 787 species. Notably, numerous species listed here are known solely from their original descriptions. With the growing interest in the taxonomy and biodiversity of Philippine scarab beetles, we anticipate the potential rediscovery of certain species and significant taxonomic revisions through the combination or splitting of the country’s currently known genera and species of scarab beetles. Ultimately, this compilation should be regarded as an evolving reference rather than a definitive work, serving as a foundation for future research and discoveries in Philippine scarab biodiversity.